PENGEMBANGAN BAHAN AJAR PEMBELAJARAN SAINS BERBASIS REKAYASA UNTUK PENDIDIKAN ANAK USIA DINI (PAUD) DI PAUD NEGERI PEMBINA 2 KOTA TEBING TINGGI - Supartik, Supartik; Yus, Anita; Setiawan, Deny (Jurnal Tematik, 2019)
This study aims to develop butterfly metemorposa teaching materials and PAUD children’s activity sheets. This type of research is research and development using the van den akker model. The results of this study indicate that the validation of textbooks and children’s activities is very good and the children’s understanding of butterfly metamorphosis teaching material has increased. This can be seen through initial tests and final tests. in the initial test of the country of Trustees 2 there were 22 children or 62.85% in the sufficient category. After the initial test carried out computer-assisted engineering learning and using textbooks and child activity sheets developed by researchers, the final test results obtained by the Trustees 2 Public PAUD were 25 or 71.42% of children or 665.72% and Pembina 3 PAUD of 25 children or 78.13% fulfill the permendikna mandate 58 of 2009, from this result there is an increase for PAUD Pembina 2 by 30% while Negeri Pembina 3 PAUD increases by 35%. So that the impact of using textbooks and child activity sheets and computer-assisted engineering learning can improve children’s learning outcomes.